2015
DOI: 10.20870/oeno-one.2015.49.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on some grapevine varieties grown in Peru for Pisco production

Abstract: Aim : The Peruvian region of Ica is an important area of grapevine cultivation, mainly for the production of pisco, the flagship hard drink of Peru. The effects of a changing climate have been assessed using the recorded temperatures of a weather station together with projected climates for the 21 st century generated under the A1B SRES scenario. Methods and results :The bioclimatic indices commonly used in grapevine studies have increased in recent years and will continue to rise along the 21 st century in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
4
0
3
Order By: Relevance
“…Numerous papers have shown that high temperatures tend to accelerate vine phenology (Yzarra et al 2015;Parker et al 2020). Even though the design of this work did not allow for a formal interpretation of these results, it is possible that the higher temperatures in the spring of the 2020 season accelerated phenology and favoured earlier shoot growth stop that year.…”
Section: Apex-vigne Application Adoption -Location Of Surveysmentioning
confidence: 84%
“…Numerous papers have shown that high temperatures tend to accelerate vine phenology (Yzarra et al 2015;Parker et al 2020). Even though the design of this work did not allow for a formal interpretation of these results, it is possible that the higher temperatures in the spring of the 2020 season accelerated phenology and favoured earlier shoot growth stop that year.…”
Section: Apex-vigne Application Adoption -Location Of Surveysmentioning
confidence: 84%
“…Su clima es típicamente árido, la duración de la insolación diaria tiene un valor medio de 7 horas. La temperatura media es de 21 ° C con una media máxima de 29°C y una media mínima de 14 ° C, y la precipitación anual es de casi cero (cantidad a largo plazo de 2 mm) (Yzarra, et al, 2015, Abreu y Bannon, 1993.…”
Section: Descripción Del áRea De Estudiounclassified
“…Change and Wine has been organized three times by the Wine Academy of Spain to address the need for climate change adaptation in viticulture (Li Y.B., 2015). Several investigations of climate change and viticulture are underway in France and other wineproducing countries (Ollat and Touzard, 2014b ;Yzarra et al, 2015). In France, the multidisciplinary LACCAVE project (long-term adaptation to climate change in viticulture and enology) involving 23 different laboratories from the National Institute for Agricultural Research of France (INRA), the National Center for Scientific Research (CNRS) and…”
Section: Collaborative Strategiesmentioning
confidence: 99%